2014
DOI: 10.1377/hlthaff.2013.0934
|View full text |Cite
|
Sign up to set email alerts
|

The Health Reform Monitoring Survey: Addressing Data Gaps To Provide Timely Insights Into The Affordable Care Act

Abstract: The Health Reform Monitoring Survey (HRMS) was launched in 2013 as a mechanism to obtain timely information on the Affordable Care Act (ACA) during the period before federal government survey data for 2013 and 2014 will be available. Based on a nationally representative, probability-based Internet panel, the HRMS provides quarterly data for approximately 7,400 nonelderly adults and 2,400 children on insurance coverage, access to health care, and health care affordability, along with special topics of relevance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 9 publications
0
66
0
Order By: Relevance
“…As discussed earlier, the response rate for rapid-turnaround data sources such as the WBI is much lower than that for government-conducted surveys. 8,9 However, Gallup polls and similar data sets are used regularly to offer timely evaluations of population-level phenomena, including health care-related issues 27,28 and elections. [29][30][31] More importantly, the WBI has been validated against government-conducted surveys for this type of analysis of the uninsured rate, although the same study concluded that the WBI does not reliably measure the type of insurance a person has.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed earlier, the response rate for rapid-turnaround data sources such as the WBI is much lower than that for government-conducted surveys. 8,9 However, Gallup polls and similar data sets are used regularly to offer timely evaluations of population-level phenomena, including health care-related issues 27,28 and elections. [29][30][31] More importantly, the WBI has been validated against government-conducted surveys for this type of analysis of the uninsured rate, although the same study concluded that the WBI does not reliably measure the type of insurance a person has.…”
Section: Discussionmentioning
confidence: 99%
“…All respondents provided information about access to care, affordability, utilization, and demographic characteristics. Survey questions were adapted from past surveys when feasible, [14][15][16] and the instrument was pilot-tested before going into the field (see Appendix for precise question wording).…”
Section: Survey Designmentioning
confidence: 99%
“…To facilitate a more nationally representative sample, a laptop and Internet service is provided to panel participants who do not have Internet connectivity at home. The KnowledgePanel has been used for a variety of health-related studies, [30][31][32] including a prior study using a methodology parallel to that presented here. 9 A sample of 2162 English-speaking panel participants was selected for the current survey.…”
Section: Samplementioning
confidence: 99%